Generation Z’s Trust in The Chatbot of Mental Health Service - Kelana, Bayu; Syaani, Rofii Asy; Kristanto, Febri; Winata, Pandu Ady (Lembaga Penelitian Universitas YARSI, 2023)
Generation Z is the age group that has experienced the most mental health-related issues due to the COVID-19 pandemic in Indonesia. Mental health information system services have become increasingly popular, so patient services are overwhelmed. Chatbot has emerged as one of the solutions to address this problem. However, conversations with them have led to social issues alongside the growing use of chatbots. This study aims to identify the factors influencing Generation Z's trust in patient service chatbots within mental health applications in Indonesia. Using the Interpretative Phenomenological Analysis method, this research analyses qualitative data from observations and interviews with five undergraduate students. Based on the analysis, the study identified seven factors that influence Generation Z's trust in chatbot customer service within mental health applications, with three being novel findings.